'Use of Operations and Supply Chain Management Strategies and Tools in Managing the Supply of Talent' - Madziba, Shemunatsi Ammon (2012)
Supply Chain Management (SCM) and Operations Managements (OM) tools and strategies are commonly used by companies operating in the production and service industries, but how far can use of these tools be stretched? This research analyses the extent to which SCM and OM tools and strategies can be used by football clubs in managing their supply of talent. The study unpacks SCM and OM theoretical frameworks to understand their applicability in a football business setting in managing the supply of elite talent. Through studying the current talent supply strategies used by different football clubs and translating them into SCM theory, this study outlines the applicability of SCM and OM strategies such as collaboration, partnerships and the use of the purchasing management tools the Kraljic Matrix and the Power Matrix to determine talent supply strategies football clubs should pursue in managing their supply of talent. Collaboration, the Extended Enterprise concept and partnerships are identified as powerful SCM strategies that make football clubs successful. The research discusses and identifies that when football clubs design their supply chains, the design strategy should be done based on the talent supply strategy that they pursue. The research findings after mapping out the football clubs talent supply processes and strategies are translated into SCM strategies. Football Clubs studied are FC Barcelona (FCB), Manchester City Football Club (MCFC) and Tottenham Hotspur Football Club (Spurs). FCB and Spurs were both identified to be working with collaborative partners in managing their supply of talent. MCFC was identified as being reliant on its strong buying power in managing its supply of talent. Because of their differences in talent supply strategies, the footballs were identified as falling into different quadrants on the Kraljic Matrix. SCM tools and strategies are recommended to be of use to other industries such as academia, Science and Engineering etc and other sporting disciplines.